Stratified analysis of clinical pregnancy outcomes of sequential embryo transfer in frozen embryo transfer cycles based on different factors: a retrospective study - Jialing Li; Jing Ji; Hua Guo; Feimiao Wang; Yunxing Fu; Rong Hu (BMC, 2023)
Abstract Objective To explore the effect of sequential embryo transfer (ET) on the pregnancy outcome of frozen-thawed embryo transfer (FET) cycle and the indications of sequential transfer. Methods A total of 1440 FET cycles were enrolled in this retrospective study, of which 1080 patients received conventional ET and 360 patients received sequential ET. Further stratified analysis was performed according to the number of previous failed cycles, the number of embryos transferred and the stage of blastocyst (day 5 or 6, denoted D5 or D6) transferred. Comparison of pregnancy rates, implantation rate, miscarriage rate and multiple pregnancy rate among the groups of patients. Results The clinical pregnancy rate and implantation rate of the sequential ET group were higher than those of the conventional ET group (P < 0.01); however, there was no statistical difference in multiple pregnancy rate and miscarriage rate (P > 0.05). In sequential transfer, the number of transferred embryos (2 or 3) and the stage of transferred blastocysts (D5 or D6) had no effect on clinical pregnancy rate, implantation rate, multiple pregnancy rate and miscarriage rate (P > 0.05). In patients with three or more previous failure cycles, the sequential ET group showed higher clinical pregnancy rate and implantation rate (P > 0.05). Conclusions Compared with conventional ET in FET cycle, sequential ET strategy could significantly improve the clinical pregnancy rate and implantation rate. In sequential transfer, patients with three embryos transferred don't have higher pregnancy rate and implantation rate. Besides, sequential transfer is more suitable for patients with repeated implantation failures (RIF), and increase the utilization rate of D6 blastocysts.